Dampak Kesehatan Kecanduan Permainan Pada Pemain Game Usia Muda : Tinjauan Sistematis - Rendi Ariyanto Sinanto; Sitti Nur Djannah (Dian Nuswantoro Semarang, 2020)
ABSTRACTGame addiction is an excessive use of the game for a long time. The World Health Organization has categorized game addiction as a mental disorder. The purpose of this study was to determine the factors that influence participants to play games, and determine the health effects of game addiction. This research was conducted on 18 to 21 April 2020 with the literature review method of the article on http://garuda.ristekdikti.go.id published in the period 2013 to 2019, according to the search there were 51 articles according to keywords and there were 14 selected articles. The results obtained by factors that influence participants to play games are there are facilities to play games at home, environmental influences, and the desire to play the game. Health effects that will arise are changes in diet and changes in sleep patterns that are not good, this will have a serious health impact on someone who is addicted to the game or gaming disorder if the behavior is maintained. For gamers to be able to limit the time to play the game a maximum of 1 hour a day, do not delay eating and drinking, do not delay urinating, and sleep at least eight hours a day.Keywords: Impact, health, addiction, gaming, adolescents.